The effectiveness of protected areas in the conservation of species with changing geographical ranges. (3rd March 2015) - Gillingham, Phillipa K.; Bradbury, Richard B.; Roy, David B.; Anderson, Barbara J.; Baxter, John M.; Bourn, Nigel A. D.; Crick, Humphrey Q. P.; Findon, Richard A.; Fox, Richard; Franco, Aldina; Hill, Jane K.; Hodgson, Jenny A.; et al.
<x xml:space="preserve">Abstract</x> A cornerstone of conservation is the designation and management of protected areas (PAs): locations often under conservation management containing species of conservation concern, where some development and other detrimental influences are prevented or mitigated. However, the value of PAs for conserving biodiversity in the long term has been questioned given that species are changing their distributions in response to climatic change. There is a concern that PAs may become climatically unsuitable for those species that they were designated to protect, and may not be located appropriately to receive newly‐colonizing species for which the climate is improving. In the present study, we analyze fine‐scale distribution data from detailed resurveys of seven butterfly and 11 bird species in Great Britain aiming to examine any effect of PA designation in preventing extinctions and promoting colonizations. We found a positive effect of PA designation on species' persistence at trailing‐edge warm range margins, although with a decreased magnitude at higher latitudes and altitudes. In addition, colonizations by range expanding species were more likely to occur on PAs even after altitude and latitude were taken into account. PAs will therefore remain an important strategy for conservation. The potential for PA management to mitigate the effects of climatic change for retracting species deserves further investigation. © 2015 The Linnean Society of London, Biological Journal of the Linnean Society, 2015, ●●, ●●–●●.